2015
DOI: 10.1097/mph.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Gene Polymorphisms and Their Relation With DNA Damage, DNA Repair, and Total Antioxidant Capacity in Childhood Acute Lymphoblastic Leukemia Survivors

Abstract: Oxidative stress and defective DNA repair are major contributory factors in the initiation and progression of carcinogenesis. Chemotherapy and radiotherapy cause oxidative DNA damage, consume antioxidant capacity, and impair DNA repair activity. These effects of chemotherapy and radiotherapy may be contributory factors in the development of secondary malignancy in cancer survivors. Basal, H2O2-induced, and postrepair DNA damage; urinary 8-hydroxydeoxyguanosine level as a marker of oxidatively damaged DNA; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Some studies have reported a strong association between the XPD Lys751Gln polymorphism and increased leukemia risk, 20 , 21 , 39 while one study found decreased risk of the leukemia. 26 In the current study, XPD Lys751Gln polymorphism was found to be associated with increased risk for CML. These results are in agreement with Bănescu et al 39 To examine the effect of gene–gene interactions as an estimation for CML risk in the present study, the relationship between dual gene–gene combinations was also analyzed.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Some studies have reported a strong association between the XPD Lys751Gln polymorphism and increased leukemia risk, 20 , 21 , 39 while one study found decreased risk of the leukemia. 26 In the current study, XPD Lys751Gln polymorphism was found to be associated with increased risk for CML. These results are in agreement with Bănescu et al 39 To examine the effect of gene–gene interactions as an estimation for CML risk in the present study, the relationship between dual gene–gene combinations was also analyzed.…”
Section: Discussionmentioning
confidence: 49%
“… 25 Nucleotide excision repair and basal transcription are carried out by helicase encoded by XPD genes and aberrations in the XPD gene predisposes to increased risk of cancer. 26 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical biochemical indices of patients with ALL showed a marked increase in the levels of malondialdehyde, an important biochemical index for plasma oxidative stress [ 70 ], and a notable increase in the levels of 8-oxodG and 8-OHdG, biomarkers of oxidative DNA damage in urine, in patients with ALL [ 71 , 72 ]. In addition, the level of oxidatively modified DNA bases in lymphocytes from children with ALL was markedly higher than that in children without the disease [ 73 , 74 , 75 ]. Abundant evidence has shown that ROS have a vital role in secondary gene events in ALL.…”
Section: The Role Of Redox Dyshomeostasis In the Occurrence Of Allmentioning
confidence: 99%
“…Increased TOS values in other types of cancer such as thyroid and colorectal cancers were also observed [ 24 , 25 ]. During anticancer therapy, a decrease of TAC was found, but in cancer survivors, this parameter was not different from that in the control group [ 26 , 27 ]. In pediatric patients with tumors, including osteosarcoma and Ewing’s sarcoma, various levels of the GSH/GSSG ratio in serum were obtained before treatment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%